Study of the thickness of the silicon dioxide on wafer using dry and wet oxidation method - Mohamad Fadzli Ali
This final year project focused on four goals: to study the dry and wet oxidation thickness, to grow a thin layer of silicon dioxide (SiO2) on Si wafer, to determine the parameter required for thickness needed, and to compare with the simulation and theoretical thickness to achieve the most accurate parameter for the thickness required.